Norma ISO 50001 Mecanismo facilitador que fortalece la gestión pública en organizaciones del Estado (2022)
The management of energy efficiency in public sector entities requires advances and tools that allow its measurement and integration into the other applicable management systems, this is how the NTC-ISO 50001: 2019 provides an adequate framework for such management. A bank of tools integrated into a web portal is proposed that revolves mainly around three elements; the first one associated with the creation of a consumption baseline, the second element is a measurement instrument integrated with the MIPG that allows establishing the degree of maturity associated with the NTC ISO 50001: 2019 controls implemented within the entity and, finally, a set of guides, formats, and guiding documents for the implementation of the EnMS published on a web portal. Result of the evaluation of experts and the application of the diagnosis and the baseline methodology, it was evidenced that the result of the research provides elements that allow evaluating the management, administration, control and continuous improvement based on the efficient use of energy and, hence, greater austerity in public spending.